THE COMPOSITIONAL AND MUSICAL COMPONENTS OF SPECIAL ARTISTRY IN RHYTHMIC GYMNASTICS - Krafte, Diana; Fernāte, Andra; Lāriņš, Viesturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Rhythmic gymnastics is an Olympic sport. Competitive composition in rhythmic gymnastics should not only meeting the requirements of the physical abilities, but being technically perfect and expressively performed by a gymnast as well. Describing the expressiveness of rhythmic gymnast’s performance, the term “special artistry” is used. Special artistry in rhythmic gymnastics means artistry of compositional content, artistry of rhythmic gymnast, shown by athlete during performance of competitional composition and gymnast’s artistic abilities, influencing aesthetical effect of composition performance. The evaluation of judges at competitions often has a subjective character that is why the actual task of research is to make the expert assessment more objective. Particular investigation in general focuses on possible solutions to make alternative judging. Thus special artistry generally is viewed in 4 components – technical, aesthetical, compositional and musical. This paper is focused only on compositional and musical components of special artistry, headlining creation, build and content of composition, its execution and compositional and musical skills of the gymnast. The aim of the research is to define and to classify competitional composition determining components criteria and exponents of special artistry in rhythmic gymnastics. To develop this research there was used the meta-analysis of scientific literature, using researches of the top rhythmic gymnastics, art and music specialists from one data base, with further creation of thematic typology of elements. In total there were screened 961 sources of which 107 qualified and 25 were chosen for further research. Investigating chosen data sources by the appropriated search terms, as a result 15 criteria and 104 exponents in compositional component, and 5 criteria and 4 exponents in musical component of special artistry in rhythmic gymnastics were determined and classified according to the selected structure of special artistry components in rhythmic gymnastics.